The covid-19 pandemic and remote teaching: the absence and need for teacher mediation in two public schools in/from the field of the southwest region of the state of Paraná - Deniz Maria Batistus; Cecília Maria Ghedini (Revista Brasileira de Educação do Campo)
This article aims to present some aspects of a Master's Dissertation research that analyzed the implications of remote teaching offered in the period of the COVID-19 Pandemic and the teaching-learning process, considering the absence and need for teacher mediation in classes developed in the form of printed activities and/or online resources, with students from two public schools in/from the countryside, in the state school system of the state of Paraná, in the years 2020 and 2021. The objective was to analyze the implications of remote teaching offered in the pandemic period to students from these two schools. The methodology was given with a qualitative approach, semi-structured interviews with teachers and students and documentary research procedures. Data analysis found that teacher mediation stood out as a necessity during remote teaching, due to its absence, as the pedagogical strategies used proved to be ineffective in teaching-learning. Thus, it appears that the mediation of teacher-student interaction is a necessity for learning and that technological resources are potential, when integrated into teaching practice as a complementary pedagogical resource, not suppressing the teacher's action in classes.